O ensino de Ciências da Natureza no contexto pandêmico: uma reflexão docente a partir do período de transição escolar nos anos iniciais para os anos finais do ensino fundamental - Peternela, Daiane Cristine (2024)
The Covid-19 pandemic in Brazil demanded changes in education, for instance, regarding the format of delivering classes, which included all curriculum components, one of them being the Science curriculum. Due to the pandemic, with the suspension of in-person classes, all students were forced to transition to remote learning. The Science curriculum, when developed with students, is considered a dynamic class. On this basis, the theme discussed here, as well as the research conducted with teachers from State schools from Paraná, such as Eleodoro Ébano Pereira State School, Padre Carmelo Perrone State School, and Marilis Faria Pirotelli State School, was motivated by reflecting on how the practice of science teachers with 6th grade students in Elementary School was from 2020 to 2022, considering they are students who were in transition from 5th to 6th grade and could have their learning of Science content compromised. Therefore, it is highlighted that this work is of bibliographical, documentary, and field order, in which semi-structured interviews were conducted with four teachers from the three previously mentioned state schools, all located in the municipality of Cascavel-PR. Thus, for data analysis, Textual Discursive Analysis (ATD), by Moraes and Galiazzi (2011), was used. Through the analysis, the aim was to understand the teachers' perception regarding Science teaching during the pandemic period and how the interaction between teacher and 6th grade students of the Elementary School occurred. Due to the teachers’ responses, it was noticed, through elaborated data categories, that in the beginning of the pandemic, the lack of electronic equipment and the lack of continuous training for the use of equipment and digital platforms were the factors that most hindered the progress of classes. Additionally, the lack of interest from students was also a contributing factor, both in remote classes and in printed activities. Regarding the teaching of Natural Sciences, after three years since the beginning of the pandemic, it is possible to perceive the damages of this period, such as difficulties in reading and writing, caused by social isolation, which at the time was necessary to contain the spread of the virus.